THE RELATIONSHIIP BETWEEN LEARNING OUTCOMES ENGLISH FOR YOUNG LEARNERS (EYL) TO ENGLISH MICROTEACHING COURSE IN UNIVERSITAS MUHAMMADIYAH SIDOARJO - ermawati Zulikhatin Nuroh; Anam Syafi'ul (Universitas Islam Nahdlatul Ulama Jepara, 2019)
This Research aims to investigate the relationship of learning outcomes English for Young Learners (EYL) to English Microteaching course of the students in elementary school teachers ' education (PGSD) Muhammadiyah Sidoarjo University and wants to know how much of the relationship between English Young Learners (EYL) learning outcomes and the teaching ability of students’ Primary Teachers Departement (PGSD). The research methodology is using a quantitative approach, with a type of non-exsperimental research study, with the Ex Post Facto approach, one-group posttest-only design. Population and Sample of this research are all students of the Primary Teachers Departement (PGSD) Universitas Muhammadiyah Sidoarjo academic year 2016-2017, amounting to 110 students. The results showed that there was a relationship or influence of study outcomes English Young Learners (EYL) to English Microteaching student Primary Teachers Departement (PGSD) is 0,555 or 55,5%. Keywords: Primary Teachers Departement, English Young Learners, Microteaching